High serum anti-Müllerian hormone concentrations have a negative impact on fertilization and embryo development rates. Issue 1 (January 2022) - Tsai, Hsiao-Wen; Liao, Pei-Fen; Li, Chia-Jung; Lin, Li-Te; Wen, Zhi-Hong; Tsui, Kuan-Hao
Abstract: Research question: What is the impact of high serum anti-Müllerian hormone (AMH) concentrations on fertilization and embryo development among infertile women undergoing treatment with assisted reproductive technology (ART)? Design: Retrospective study of 1036 infertile women undergoing ART; women were divided into three groups according to serum AMH concentrations: AMH <1.1 ng/ml, 1.1–5.0 ng/ml and >5.0 ng/ml. The fertilization and embryo development rates of patients with different AMH concentrations and after stratification according to age were compared. Results: Women with high AMH concentrations were younger and had higher testosterone concentrations (0.4 ± 0.13 versus 0.3 ± 0.12 versus 0.3 ± 0.08 µg/dl, P < 0.001) than women with low AMH concentrations. However, analysis of the embryo development rate showed negative outcomes for women with high AMH concentrations, including a poor fertilization rate (76.3 ± 17.36 versus 82.1 ± 19.15 versus 82.4 ± 25.38, P = 0.003), and poor day 3 embryo development rate (55.6 ± 23.88 versus 62.6 ± 26.52 versus 62.8 ± 32.65, P = 0.014). Multivariate linear regression analysis showed significantly negative correlations of the AMH concentrations with the fertilization rate ( P < 0.001) and day 3 embryo development rate ( P = 0.006). Subgroup analysis showed that age 30 years or younger had a significant negative correlation with AMH and the embryo development rate, including the fertilization rate ( P < 0.001) and day 3 embryo development rate ( P = 0.037). Conclusion: These results suggest that high serum AMH concentrations, contributing to a hyperandrogenic environment and leading to decreased oocyte developmental competence, may have a negative impact on fertilization and the early stage of embryo development in women undergoing treatment with ART.